2005
DOI: 10.1080/02607470500169006
|View full text |Cite
|
Sign up to set email alerts
|

‘They think that swearing is okay’: first lessons in behaviour management

Abstract: Despite a considerable body of literature devoted to the 'behaviour management' of pupils, there is little that actually considers the experience of beginning teachers in learning to cope with that behaviour. Here we consider the experience of student teachers and illustrate their attempts to form deeper understanding, connections between theory and practice and the contribution made by other teachers. It is argued that students at this first stage of classroom teaching experiences are, despite the inevitable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 13 publications
2
19
0
Order By: Relevance
“…In terms of what student teachers actually learnt as a result of engaging in this compulsory activity, the postings indicate an extensive sharing of behavioural tips, confirming earlier studies which found that student teachers want step-by-step strategies to manage classroom behaviour (Bromfield, 2006;McNally, I'anson, Whewell & Wilson, 2005). There was some, albeit little, evidence of student teachers' reflecting about the nature of behaviour and misbehaviour in the classroom and the linking of theory and practice.…”
Section: Discussionsupporting
confidence: 68%
“…In terms of what student teachers actually learnt as a result of engaging in this compulsory activity, the postings indicate an extensive sharing of behavioural tips, confirming earlier studies which found that student teachers want step-by-step strategies to manage classroom behaviour (Bromfield, 2006;McNally, I'anson, Whewell & Wilson, 2005). There was some, albeit little, evidence of student teachers' reflecting about the nature of behaviour and misbehaviour in the classroom and the linking of theory and practice.…”
Section: Discussionsupporting
confidence: 68%
“…According to McNally et al (2005), no matter how effectively pre-service teachers are prepared, they still face huge challenges as beginning teachers because they 'do not have the experience or developed instinct for reading the situation'. They suggested they 'need an early period in which there is a tolerance of judgment calls and mistakes, in relation to behaviour management at least ' (p. 177).…”
Section: Australian Journal Of Teacher Educationmentioning
confidence: 99%
“…JET has previously published disturbing findings regarding bullying in higher education (see Kyriacou et al 2007;Maguire 2001;Sewell et al 2009) as well as research into behaviour management (e.g. McNally et al 2005), but Yariv's paper deals with a slightly different topic: discipline issues within a college. It might come as a surprise to the outsider that a teachers' college should have discipline problems as this is the very place one would expect to find approaches identifying ways in which discipline issues can be resolved.…”
Section: Editorialmentioning
confidence: 96%